The evolution of social media in nephrology education: A mini-review - Shankar, Mythri; Sparks, Matthew A. (Frontiers in Nephrology, 2023)
Social media is defined as "a group of Internet-based applications that build on the ideological and technological foundations of Web 2.0, and that allow the creation and exchange of user-generated content". Social media in education is the use of this platform to enhance knowledge sharing among the peer groups. In the early 1990s, CD-ROMs came into the picture followed by the internet in the 2000s. The internet revolutionized learning by opening up the windows of knowledge. Ever since social media platforms have taken over our day-to-day lives. 95% of students have access to smartphone and 45% are online constantly. The internet provides more resources for learning and research. Social media platforms are powerful tools to spread knowledge by the way of stories, videos, feeds, and educative games. Both formal and informal learning can be achieved with social media. Twitter is used to discuss journal clubs, share infographics and visual abstracts of original research work. With multiple responsibilities, it is difficult for women in nephrology to connect and travel to make a physical presence. Women in nephrology can connect via webinars on zoom platforms. This helps in networking and collaborating with fellow nephrologists across the globe outside their own institutions. Social media have limitations as well. Insensitive posts can have a detrimental effect on one’s career. A survey has shown that increased use of social media can cause addiction, anxiety, lack of self-esteem, and depression among youngsters. Hence, effective use of social media should be individually motivated toward a positive goal.